Independensi Lembaga Pengawas: Kunci Efektivitas Undang-Undang Perlindungan Data Pribadi - Hs, Fatimah; Rahmatullah, Nursalam; Hamsah, Hamsah; Hasmiati, Hasmiati (Universitas Jambi, Fakultas Hukum, 2025)
This study aims to analyze the implementation of personal data protection under Law Number 27 of 2022 and to examine the urgency of establishing an independent supervisory authority for personal data protection. The research employs a normative juridical approach by reviewing primary and secondary legal sources as well as relevant literature, then analyzed descriptively to identify regulatory and institutional weaknesses. The findings indicate that although Law Number 27 of 2022 marks a significant step in protecting personal data in Indonesia, its provisions remain partial due to the absence of an independent supervisory body. The lack of such authority may undermine law enforcement, as a body directly under the president is vulnerable to political and bureaucratic interests. This study emphasizes that an independent supervisory institution is essential to ensure legal compliance, the enforcement of sanctions, and the effective protection of citizens’ privacy rights. Therefore, the establishment of an autonomous supervisory authority is urgent to realize the objectives of the Personal Data Protection Law in ensuring justice, legal certainty, and utility.